CIP: an alternative career guidance model to improve self-understanding and work understanding for deaf students - Endang Pudjiastuti Sartinah; Esa Nur Wahyuni; Eryana Fatimasari Retno Budiati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The Cognitive Information Processing (CIP) career guidance model is an approach that emphasizes the reconstruction of the mind to achieve self-understanding and understanding of work. This research examines the CIP career guidance model to improve self-understanding and work understanding in deaf students. This research uses a single-subject design with a pretest-posttest on 12 deaf students in Indonesia. Data collection uses the self-understanding and work understanding Instrument developed by researchers, intervention workbooks, observation instruments, and interviews. Data analysis of this study using non-parametric statistics with the Wilcoxon Test. The results showed that CIP, a career guidance model for deaf students, can improve the knowledge and skills of self-understanding and work understanding. Thus, CIP can be used as a career guidance model for deaf students to improve their self-understanding and work understanding.